The impact of online banking on customer service delivery in the Malaysian banking industry : Kano's model approach / Alhaji Abubakar Aliyu … [et al.] - Aliyu, Alhaji Abubakar; Tasmin, Rosmaini; Takala, Josu; Che Rusuli, Muhammad Saufi; H., Norazlin (Faculty of Information Management, 2014)
This study is about the impact of online banking on customer service delivery in Malaysian banking industry. Due to the challenges of globalization and intensive competition, Banks were compelled to comprehend the services of online banking in order to entice the existing and the potential customers. Although, the level of awareness is relatively high; but still only 64% patronize online banking in Malaysia. It is against this background that this paper seeks to examine the significant factors that may cause online banking to have an impact on customer service delivery with the ultimate aim of either accepting or rejecting any preconceived idea of the researcher. The study employed some hypotheses in order to guide the research in achieving the overall aim of the research as well as testing the stated hypotheses. Behavioral factors such as security, convenience and cost were the main concern of the respondents towards effective service delivery. The study reveals that "Cost" is the major driver of effective service delivery of online banking services in Malaysia. Equally, the study also explores various implications of the research.